Group Types and Characteristics According to Changes in Levels of Perceived Career Barriers by Multicultural High School Students in Korea - 배선희; 손은영 (KEDI journal of educational policy, 2025)
This study aims to divide multicultural high school students into groups according to the changes in their perceived career barriers, analyze their predictive factors, and suggest measures to reduce their perceptions of career barriers. K-means cluster analysis and multinomial logistic regression analysis were conducted using the 7th to 9th waves of the 1st Multicultural Youth Panel Survey (MAPS) of the Korea Youth Policy Research Institute The four group-specific influencing factors were identified as achievement motivation, self-esteem, father's support and interference in career-related behavior, lack of involvement, mother's support, communication with parents, relationship with teachers, relationship with peers, and school adjustment: academic. The significance of this study lies in providing foundational data and exploring ways to reduce perceived career barriers among multicultural high school students. KCI Citation Count: 0